Visual Analytics: Need, Process, Scope, Tools & Techniques and Challenges - Shankar, R; Duraisamy, S (International Journal of Computer Sciences and Engineering, 2025)
Visual analytics employs interactive visualizations to integrate users’ knowledge and inference capability into numerical/algorithmic data analysis processes. It is an active research field that has applications in many sectors, such as security, finance, and business.. This paper aims at providing an overview of visual analytics, need, scope, tools and techniques and the most important technical research challenges in the field